Implicative Int-Soft Filters of R0-Algebras - Young Bae Jun; Sun Shin Ahn; Kyoung Ja Lee (Discrete Dynamics in Nature and Society)
The notion of implicative int-soft filters is introduced, and related properties are investigated. A relation between an int-soft filter and an implicative int-soft filter is discussed, and conditions for an int-soft filter to be an implicative int-soft filter are provided. Characterizations of an implicative int-soft filter are considered, and a new implicative int-soft filter from an old one is displayed. The extension property of an implicative int-soft filter is established.